2019
DOI: 10.3390/genes10050394
|View full text |Cite
|
Sign up to set email alerts
|

Three New Integration Vectors and Fluorescent Proteins for Use in the Opportunistic Human Pathogen Streptococcus pneumoniae

Abstract: Here, we describe the creation of three integration vectors, pPEPX, pPEPY and pPEPZ, for use with the opportunistic human pathogen Streptococcus pneumoniae. The constructed vectors, named PEP for Pneumococcal Engineering Platform (PEP), employ an IPTG-inducible promoter and BglBrick and BglFusion compatible multiple cloning sites allowing for fast and interchangeable cloning. PEP plasmids replicate in Escherichia coli and harbor integration sites that have homology in a large set of pneumococcal strains, inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…Finally, transformation efficiencies were quantified by flow-cytometry ( Figure 4A). In line with studies using classical plating methods to assess transformation efficiencies (Keller et al, 2019;Lee et al, 1998), higher transformation frequencies were observed at higher donor DNA concentrations and with longer homology regions ( Figure 4B). Interestingly, the frequency of transformation plateaued at ~50% regardless of the concentration of donor DNA and sequence homology length ( Figure 4B).…”
Section: Single Cell Quantification Of Homeologous Recombination Highsupporting
confidence: 85%
See 2 more Smart Citations
“…Finally, transformation efficiencies were quantified by flow-cytometry ( Figure 4A). In line with studies using classical plating methods to assess transformation efficiencies (Keller et al, 2019;Lee et al, 1998), higher transformation frequencies were observed at higher donor DNA concentrations and with longer homology regions ( Figure 4B). Interestingly, the frequency of transformation plateaued at ~50% regardless of the concentration of donor DNA and sequence homology length ( Figure 4B).…”
Section: Single Cell Quantification Of Homeologous Recombination Highsupporting
confidence: 85%
“…In order to overcome these concerns and analyze successful recombination events during transformation at the single-cell level, we developed a fluorescence-based reporter system inspired by a system previously used to observe natural transformation in S. pneumoniae ( Bergé et al, 2013 ) and other bacterial species ( Boonstra et al, 2018 ; Corbinais et al, 2016 ; Godeux et al, 2018 ). To do so, we utilized a fluorescent donor strain in which the gene encoding the abundant histone-like protein HlpA (aka HU) was fused in frame with the gene encoding the red fluorescent protein mScarlet-I integrated at the native hlpA locus at 169° on the circular chromosome ( Keller et al, 2019 ) (strain VL1780) ( Figure 3A ). A recipient, non-fluorescent strain was constructed (strain VL1784) in which hlpA was separated from mScarlet-I by a stop codon mutation (G > T) ( Figure 3A–C and Figure 3—figure supplement 2A , hlpA-stop-mScarlet-I ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumococci are emerging as a preferred model organism for these surface structure studies because of its acknowledged clinical importance as a human pathogen and because of its inherent genetic malleability. For instance, the expression of pce can be regulated by inducible promoters [24,36] and DBA can be used to identify the subcellular location where Pce functions. Thus, these lectins will help us study the synthesis and attachment of WTA/LTA to PG.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli library could also be used as a reservoir of sgRNAs for construction of reproducible CRISPRi 190 libraries among S. pneumoniae D39V strains with different genetic backgrounds (e.g. mutant strains) or to transform 191 other pneumococcal strains that contain the pPEPZ integration region, which is harbored by 64.21% of all sequenced 192 pneumococcal strains (Keller et al, 2019). The plasmid pool was then transformed into S. pneumoniae D39V with the 193 above described tet-inducible dcas9 ( Figure 2E).…”
mentioning
confidence: 99%